A Comparative Study of Serum Thyroxine, Tri-Iodothyronine and Thyrotropin Between Low Birth Weight and Normal Birth Weight Neonate (Journal of Dhaka National Medical College & Hospital, 2016)
This was a prospective randomized study. The period of study was from April 2005 to May 2006 and conducted in the department of Pediatrics and obstetrics in BSMMU, in DMCH and in the Institute of nuclear Medicine (INM). A total of 90 neonates of either sex of postnatal age ranging from 3-6 days were selected for this study. They were divided into three groups of 30 preterm LBW (gestational age < 37weeks & birth weight